Pengembangan Video Tutorial Sport Massage - Nainggolan, Jefrinto Welsius; Hadinata, Reza; Diana, Fitri (SPRINTER: Jurnal Ilmu Olahraga, 2025)
Sport Massage is a massage therapy designed to help athletes maintain their physical, physiological, and psychological condition. This research aims to create a Sport Massage tutorial video for physical education and health students and to determine the effectiveness of the Sport Massage tutorial video. The research method used in this study is Development. The research development model used is ADDIE. Data collection techniques use validation forms from material experts and media experts as well as questionnaires to students in 3 stages: small scale with 15 students, large scale with 35 students, and effectiveness testing with 20 students at Jambi University. The results of this research at Jambi University showed that the material expert validation assessment obtained 90% or very good, then the phase 1 media expert assessment obtained 70% or good, and the phase 2 media expert assessment obtained 84% or very good. After that, the effectiveness test obtained a result of 92% or very good. The researcher can conclude that the Sport Massage tutorial video can be categorized as very good.